Petrografia, geoquímica e modelagem geológica/geoquímica da porção central do Alvo Fósforo-Uranífero Mandacarú, Irauçuba-CE - Cardoso, Alan Dantas (2022)
The Mandacaru target (Irauçuba-CE), besides the Serrotes Baixos, Taperuaba occurrences and the Itataia deposit are part of the Uranium-Phosphorus Province which occurs in the Center-Northen part of the Ceará state. Those rocks are part of the Central Ceará Domain, northern part of the Borborema Province, mostly a result of the convergence and collision of Archean and Paleoproterozoic crust and major adjacent cratonic areas during the Brazilian/Pan-African Orogeny. We present new structural, mineralogical and chemical data from the Mandacaru target rocks, using drillhole samples, aiming to understand the main geological processes registered in the rocks and to classify and quantify the phosphorus and uranium mineralization. Seven groups of rocks were identified: (1) paragneisses, (2) impure marbles, (3) quartzites (4) cataclasites/breccias; (5) hydrothermalites; (6) colofanites and (7) ground cover and saprolite with vein quartz. Amphibolite facies mineral assemblage was identified, although intense retrometamorphism interfere in a more accurate determination. Retrometamorphism and sodium metasomatism is evidenced by biotite chloritization, albitization of feldspars, riebeckitization of amphiboles and hematitization, in addition to subsequent sericitization and saussortization of albite. Whole rock geochemical analysis led to the identification of 35 mineralized zones, with thickness of the zones varying between 60 cm and 18 m, with P2O5 and U values reaching 15.11% and 8380.39 ppm respectively. Zones that stand out, have thickness greater than 10 meters and a P2O5 and U content greater than, or close to 10% and 1000 ppm, respectively. The mineral chemistry showed that the ore mineral colophane, chemically is fluorine-apatite of amorphous nature, with P2O5, CaO and F content ranging from 36.46 to 42.18%, 50.56 to 56 .69%, 1.23 to 2.22% respectively. A mineral of SiO2 and UO3 was identified, ranging from 13.90 to 26.49% and 55.12 to 77.47% respectively. It is believed to be coffinite, however more accurate techniques are necessary to identification and classification. The geological/geochemical modeling showed that the studied area has 67.08% of sterile material and 32.92% of mineralized phosphorus material, with a content greater than 4%. With regard to volume, 90.88% is composed of sterile rocks, while 9.12% is composed of mineralized rocks. The mineralization is geographically concentrated and arranged close to the surface, which are positive points for a future open pit mine. The Mandacarú target rocks have similarities with the Itataia Deposit rocks, since both are located in a similar geological/geographic context, and in both the mineralization is linked to albitization (sodic metasomatism), associated to hydrothermal fluids. However, higher P2O5 and U contents in Itataia can be explained by better structural conditions for ore concentration, in addition to a possible low effectiveness of some of the mineralizing phases in the Mandacarú target. Further studies on mineral chemistry, fluid inclusions and isotopic geochemistry are recommended, aiming to improve the understanding of the mineralization processes and disparities between deposits.